SENTENCES WITH BOTH INDIRECT OBJECT AND VERB PARTICLES / DOLAYLI NESNE VE EYLEM PARTİKELİ İÇEREN CÜMLELER - Ayşe ÖZÇİMEN (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
This study deals uıith English sentences uuith both direct object and indirect object and ditransitive verb partide. Considering the English sentence structure, subject-verb- objed, one can make six sentences using the same verb by moving around the object and the partide. Not ali of these combinations are accepted as grammatical. In order to determine ıvhich combinations are acceptable, five speakers of English are asked to mark a number of sentences construded from phrasal verbs, for acceptability. Participants prefer sentences ıvhere the particles are placed in position of least focus. --- Bu çalışma, dolaysız ve dolaylı nesne; çift geçişli yüklem partikellerinden oluşan İngilizce cümleleri içermektedir. Özne-yüklem-nesne dizimi göz önünde tutularak İngilizce cümle yapısı içinde aynı yüklemle nesne ve partikelin yerleri değiştirilerek altı cümle kurulabilir. Ancak bu cümlelerin hepsi dilbilgisel değildir. Bu cümlelerden hangilerinin kabul edilebilir olduğunu belirlemek için ana dili İngilizce olan beş kişiye başvurulmuştur. Katılımcılar, bu cümleler içerisinde partikellerin en az vurgulu olduğu yapılara yönelmişlerdir.